Human-AI collaborative decision-making as an organization design problem - Phanish Puranam (Journal of Organization Design, 2021)
The promise of collaboration between humans and algorithms in producing good decisions is stimulating much experimentation. Drawing on research in organization design can help us to approach this experimentation systematically. I propose typologies for considering different forms of division of labor between human and algorithm as well as the learning configurations they are arranged in, as basic building blocks for this endeavor.
Keywords: 650; AI; Organization design; Machine learning; Learning configurations; Division of labor